PPost abortion contraceptive behavior among Indian women - Kumari, Nutan; Dutta, Mili; Shekhar, Chander (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Unsafe induced abortion contributes significantly to maternal morbidity and mortality. Irrespective of availability of contraceptive services women still seek for repeated induced abortion. This study examined the contraceptive behavior of currently married women who had induced abortion. Methods: Third round of District Level Household and Facility Survey (DLHS-3, 2007-2008) data is used for the study. Bivariate analysis and multivariate logistic regression method were used to examine the contraceptive behavior of women. Results: Contraceptive use is 4.6 percent among women who had at least one induced abortion. Attitude toward the use of contraceptive was found significant among women aged 25-34, who had one and two or more children, urban women, non-poor, couple both literate and women exposed to mass media. Conclusions: This study suggests the need for proper post-abortion contraception counseling and availability of multiple choices of modern methods of contraceptive among women.